2013
DOI: 10.1007/s11356-013-1787-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and bioanalytical characterisation of PAHs in risk assessment of remediated PAH-contaminated soils

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are common contaminants in soil at former industrial areas; and in Sweden, some of the most contaminated sites are being remediated. Generic guideline values for soil use after so-called successful remediation actions of PAH-contaminated soil are based on the 16 EPA priority pollutants, which only constitute a small part of the complex cocktail of toxicants in many contaminated soils. The aim of the study was to elucidate if the actual toxicological risks of soil samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…However, their efficacies were less, 108% to 115% of TMI compared with 160% to 180% of TMI for benzo[a]fluorene and benzo[a]fluorenone analyzed in the present study. This superinduction phenomenon has also been reported in the bioanalysis of environmental PAH‐contaminated samples using the H4IIE‐luc assay but also in other bioassays based on other cell lines . Sotoca et al showed that genistein could impact and stabilize the luciferase signal in estrogen‐receptor mediated assays.…”
Section: Discussionmentioning
confidence: 55%
“…However, their efficacies were less, 108% to 115% of TMI compared with 160% to 180% of TMI for benzo[a]fluorene and benzo[a]fluorenone analyzed in the present study. This superinduction phenomenon has also been reported in the bioanalysis of environmental PAH‐contaminated samples using the H4IIE‐luc assay but also in other bioassays based on other cell lines . Sotoca et al showed that genistein could impact and stabilize the luciferase signal in estrogen‐receptor mediated assays.…”
Section: Discussionmentioning
confidence: 55%
“…Relying on this list in the analysis of petroleum contaminated sediments for a toxicity estimate was said to "grossly underestimate the load of PAH contamination" (4). Based on the comparison of chemical and bioanalytical characterization of PAH contaminated soils, it was concluded that "[t]he current risk assessment method for PAH-contaminated soil in use in Sweden along with other countries, based on chemical analysis of selected PAHs, is missing toxicologically relevant PAHs and other similar substances" (5). Another study reached the conclusion that " [r]isks to wildlife were underestimated by 40 to 70 times by only considering parent PAHs" (6).…”
Section: Limitations Of the 16 Epa Pah Listmentioning
confidence: 99%
“…These sites can contain mixtures of PAHs and other important polycyclic aromatic compounds (PACs), such as alkyl‐substituted PAHs and heterocyclic compounds, which are not included in analyses of the priority PAHs (Andersson and Achten ). Previous research has shown that risk assessments based only on priority PAHs underestimate the load of PAH contamination and overlook potential contaminants present in the environment (Andersson et al ; Larsson et al ). Alkylated PAHs and heterocyclic compounds have been detected in soils, rivers, and sediments (Lundstedt et al ; Vondrácek et al ; Wayland et al ; Sun et al ).…”
Section: Introductionmentioning
confidence: 99%